Isolation of Secondary Metabolite Compounds from the Soft Coral Isis sp., Antimicrobial Testing and Molecular Docking Studies - Imran; Fajri Fitra Amalia; Sahidin; Agung Wibawa Mahatva Yodha; Nohong; I Wayan Sutapa; Thamrin Azis (Jurnal Penelitian Pendidikan IPA, 2025)
Soft coral Isis sp. is a type of soft coral that contains many chemical compounds with various benefits that have not been widely studied. This study aims to identify and isolate secondary metabolite compounds contained in the ethyl acetate extract fraction of Isis sp. soft coral, determine of antimicrobial activity, and molecular docking study. Compound separation was carried out by maceration followed by fractionation using Liquid Vacuum Chromatography (LVC). The fractions obtained were identified by Liquid Chromatography Tandem-Mass Spectrometry (LC-MS/MS) technique. Four compounds were successfully identified through LC-MS/MS analysis namely Deoxyadenosine (C10H13N5O3), Spinasterol (C29H48O), Pseudoionone (C11H16O) and Isosalsoline (C11H15NO2). Antimicrobial activity test was conducted against Staphylococcus aureus, and Escherichia coli. The results of the antimicrobial activity test showed strong activity against S.aureus bacteria and E. coli bacteria with the same MIC value of 2 µg/mL. Based on molecular docking analysis can be predicted that compounds isolated from soft coral Isis sp., namely pseudoinone compounds have a role as anti-bacterial S. aureus (PDB: 6KVS). This compound also shows a strong ability as an anti- gram positive bacteria than gram negative. Isosalsoline compounds have a role as anti-bacterial E. coli (PDB: 5BNM). This compound also shows a strong ability as an anti-gram negative bacteria rather than gram positive.